Achievement involvement and stress coping in elite wrestling - Kristiansen, E.; Roberts, C. G.; Abrahamsen, F. E. (Scandinavian Journal of Medicine & Science in Sports, 2008)
The present study explored the relationship between task involvement and coping with stress in elite competition. Participants were 82 elite wrestlers, both male (n=60) and female (n=22), from four different European countries, age 16-37. The data for the study were gathered over an 18-month period, and both qualitative in-depth interviews (n=6) and quantitative approaches were used. The quantitative study measured motivation from an achievement goal theory perspective: achievement goal orientation [Perception of Success Questionnaire], perceptions of the motivational climate [Perceived Motivational Climate in Sport Questionnaire] and coping strategies (Brief COPE). The qualitative part explored motivation and coping in depth. As expected, task involved wrestlers coped better in competitive situations due to their use of more adaptive coping strategies. The wrestlers' experiences seemingly make them prefer to stay task involved and use adaptive coping strategies (both problem-focused and emotion-focused strategies) in competition.